Dataset - Encuesta sobre residuos sólidos de construcción [Dataset] ﻿ - Rondinel Oviedo, Daniel Ricardo (2018)
Conjunto de datos del artículo: Rondinel-Oviedo, D. R. (2023). Construction and demolition waste management in developing countries: a diagnosis from 265 construction sites in the Lima Metropolitan Area. International Journal of Construction Management, 23(2), 371–382. https://doi.org/10.1080/15623599.2021.1874677